A novel direct reduction method to synthesize ordered Fe-Pt alloy nanoparticles. Issue 4 (April 2019) - Zheng, Q.; Zhang, Z.R.; Du, J.; Lin, L.L.; Xia, W.X.; Zhang, J.; Bian, B.R.; Liu, J.P.
Abstract: In this work, a direct green solid-phase reduction method for the fabrication of large yield of ordered phase Fe-Pt alloy nanoparticles was reported, in which inorganic salts were used as metal precursors and H2 -containing atmosphere was used as reducer. Utilizing this method, the composition and chemical ordered phase, such as L12 -Fe3 Pt, L12 -FePt3, and L10 -FePt phases can be easily achieved by one step reaction. The synthesized nanoparticles have clean surface because no organic precursors, no organic solutions or organic surfactants/ligands were used. Their magnetic performance and the formation mechanism of Fe-Pt alloy nanoparticles were also investigated. This strategy can be applied to synthesize many other types of alloy nanoparticles with desired composition and necessary crystal structure, which can be used for a variety of practical applications, such as in magnetism and catalyst research fields.